EFEKTIVITAS PENEGAKAN HUKUM TERHADAP LARANGAN MEMBUANG SAMPAH DI BIBIR PANTAI PESISIR LAMONGAN MENURUT PASAL 29 AYAT (1) HURUF E UNDANG-UNDANG NOMOR 18 TAHUN 2008 TENTANG PENGELOLAAN SAMPAH - Susisno, Tulung (NOVUM : JURNAL HUKUM, 2017)
Environmental pollution has become a complicated issue right now. Environmental pollution is caused by poor waste management systems and law enforcement in less effective waste management. Pollution is like what happened in the coastal areas of Brondong Regency that has been contaminated by household waste. Household waste discharged into the sea by irresponsible communities has not received serious responses from law enforcement agencies and institutions authorized to take action against the pollution. This study aims to determine the effectiveness of law enforcement Article 29 paragraph (1) sub-paragraph e of Law Number 18 Year 2008 on Waste Management in coastal areas Brondong District Lamongan and to know the obstacles experienced in enforcing the law. The type of this research is sociological juridical law research. Data were collected using interview techniques and documents. Interview conducted to the Chief of Police Pamong Praja, Head of Waste Management and Waste B3 and Rukun Fisherman Lamongan District. The result of the research shows that law enforcement of Article 19 juncto 26 of Local Regulation Number 10 Year 2010 about waste management (Perda 10/2010) in coastal area of ​​Brondong Regency of Lamongan Regency is not effective because there are three legal factors that hamper law enforcement Article 19 juncto 26 Perda 10/2010. The Lamongan District Work Unit which handles waste management issues does not enforce the Local Regulation and does not carry out the garbage disposal operation in the coastal area of ​​Brondong Regency. Factors that become obstacles and barriers to law enforcement Article 19 juncto 26 Perda 10/2010 among others are law enforcement factors, facility factors, and cultural factors.Keywords: Coastal Coast, Living Environment, Law Enforcement, Effectiveness.